Simulations of the Milky Way’s central molecular zone: I. Gas dynamics - Treß, Robin G.; Sormani, Mattia C.; Glover, Simon; Klessen, Ralf S.; Battersby, Cara D.; Clark, Paul C.; Hatchfield, H. Perry; Smith, Rowan J. (Monthly notices of the Royal Astronomical Society, 2020)
We use hydrodynamical simulations to study the Milky Way’s central molecular zone (CMZ). The simulations include a non-equilibrium chemical network, the gas self-gravity, star formation, and supernova feedback. We resolve the structure of the interstellar medium at sub-parsec resolution while also capturing the interaction between the CMZ and the bar-driven large-scale flow out to $R\sim 5\, {\rm kpc}$. Our main findings are as follows: (1) The distinction between inner (R ≲ 120 pc) and outer (120 ≲ R ≲ 450 pc) CMZ that is sometimes proposed in the literature is unnecessary. Instead, the CMZ is best described as single structure, namely a star-forming ring with outer radius R ≃ 200 pc which includes the 1.3° complex and which is directly interacting with the dust lanes that mediate the bar-driven inflow. (2) This accretion can induce a significant tilt of the CMZ out of the plane. A tilted CMZ might provide an alternative explanation to the ∞-shaped structure identified in Herschel data by Molinari et al. (3) The bar in our simulation efficiently drives an inflow from the Galactic disc (R ≃ 3 kpc) down to the CMZ (R ≃ 200 pc) of the order of $1\rm \, M_\odot \, yr^{-1}$, consistent with observational determinations. (4) Supernova feedback can drive an inflow from the CMZ inwards towards the circumnuclear disc of the order of ${\sim}0.03\, \rm M_\odot \, yr^{-1}$. (5) We give a new interpretation for the 3D placement of the 20 and 50 km s−1 clouds, according to which they are close (R ≲ 30 pc) to the Galactic Centre, but are also connected to the larger scale streams at R ≳ 100 pc.
Gesehen am 19.01.2021